PENGEMBANGAN MEDIA PEMBELAJARAN FLIPBOOK BERBASIS CANVA DALAM MENINGKATKAN HASIL BELAJAR PENDIDIKAN PANCASILA KELAS IV SD NEGERI CABEAN 2 DEMAK - Rahmawati, Naila; Andaryani, Eka Titi (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2025)
This research is motivated by students' low understanding of the content of Pancasila Education Pancasila material. Lack of interesting use of learning media and students lack of awareness to read textbooks. Based on these problems, this study has the aim of developing Canva-based Flipbook learning media to influence student learning outcomes in the Pancasila Education content of Pancasila material in class IV. This research uses a research and development method with the ADDIE model. The media was developed using the Canva application and validated by material experts and media experts. The validation results showed that the media obtained very high feasibility, with a score of 95% from material experts and 89.7% from media experts. The field trial showed an increase in student learning outcomes after using the media, with a teacher response of 98.5% (very effective) and a student response of 83.7% (very effective). The findings of this study indicate that the Canva-based Flipbook media developed in accordance with student needs and learning objectives, is able to create interesting learning, improve concept understanding, so as to improve student learning outcomes. Therefore, this media is declared feasible and effective for use in learning Pancasila Education in elementary schools.